2016
DOI: 10.1002/adhm.201600359
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Heterojunction Carbon Nanotubes Synergizing with Photoimmobilized IGF‐1 Inhibit Cellular Senescence

Abstract: Synthesis of artificial and functional structures for bone tissue engineering has been well recognized but the associated cell senescence issue remains much less concerned so far. In this work, surface-modified polycaprolactone-polylactic acid scaffolds using self-assembled heterojunction carbon nanotubes (sh-CNTs) combined with insulin-like growth factor-1 are synthesized and a series of structural and biological characterizations are carried out, with particular attention to cell senescence mechanism. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“… 162 , 163 Studies found that insulin receptor (IR) blockage, deletion of insulin receptor substrate 1 (IRS1), and/or IRS2 contribute to inhibiting MSC senescence or functional restoration of aging MSCs. 164 , 165 As for the TGF-β signaling, members of the TGF-β family ligands are key components of the stem cell niche and orchestrate diverse responses in different types of stem cells, including MSCs. 166 Transforming growth factor-β has been shown to accelerate aging by activating p16 INK4A and p21 CIP1/WAF1 .…”
Section: Mechanisms Of Msc Senescencementioning
confidence: 99%
“… 162 , 163 Studies found that insulin receptor (IR) blockage, deletion of insulin receptor substrate 1 (IRS1), and/or IRS2 contribute to inhibiting MSC senescence or functional restoration of aging MSCs. 164 , 165 As for the TGF-β signaling, members of the TGF-β family ligands are key components of the stem cell niche and orchestrate diverse responses in different types of stem cells, including MSCs. 166 Transforming growth factor-β has been shown to accelerate aging by activating p16 INK4A and p21 CIP1/WAF1 .…”
Section: Mechanisms Of Msc Senescencementioning
confidence: 99%
“…Chen et al synthesized surface-modified PCL-PLA acid scaffolds using a combination of self-assembled heterojunction CNTs and insulin-like growth factor-1 (IGF1). They investigated cellular senescence and the possible underlying mechanism by characterizing the functionality and cell biology features of these scaffolds and demonstrated the anti-senescence functionality of the self-assembled heterojunction CNT-modified scaffolds in bone tissue engineering, being able to accelerate bone healing with extremely low in vivo toxicity [82]. Park et al suggested a new method for the biosynthesis of a CNT-based 3D scaffold by in situ hybridizing CNTs with bacterial cellulose (BC).…”
Section: Carbon Nanotubes In Bone Tissue Engineeringmentioning
confidence: 99%
“…Aside from composited with polymers, CNTs were also directly coated onto polymer scaffold in which osteogenic differentiation was accelerated while cell senescence was reduced. The CNTs‐coated polymer scaffold, in conjunction with insulin‐like growth factor‐1 (IGF‐1) and MSCs, were able to repair bone defects efficiently and normally ( Figure ) …”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…C) X‐ray assay exhibiting bones healing with different scaffolds after 28 days of implantation. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%